Pengembangan LKPD Materi Penyajian Data Berbasis Lectora Inspire dengan Pendekatan CTL di Sekolah Dasar - Pratiwi Tasrif, Nada Clara; Ariani, Yetti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research starts from the reality in the field that teachers have not fully developed the Student Worksheets. This research was conducted in class IV SD Plus Marhamah, Padang City. Development of Student Worksheets Based on Lectora Inspire with the Contextual Teaching and Learning approach Presentation Material Data in SD IV SD Plus Marhamah Padang City refers to the model proposed by Borg & Gall. The results of the research developed, the results of the validity level of the Student Worksheets obtained an average validation of 4.74 with a very valid category. Furthermore, the results of testing the practicality of Student Worksheets are stated to be very practical. This can be seen from the results of teacher responses that have been implemented to get 91.67 results with a very practical category and the results of student responses amounting to 87.73 in a very practical category. Thus, the Lectora Inspire-based Student Worksheet with the Contextual Teaching and Learning approach for the presentation of the data developed was declared very valid and very practical and feasible to use.